# Calculus Answer Confirming Not Sure Im Right Help?

Evaluate the lim

a. lim x--> 64 (cube root x-4/x-64)

(∛x-4)/(x-64) -> 0/0

so then

let cube root x = u

u-4/u^3-64

u-4/u^3-64 = u-4/u-4(u^2+4u+16)

the u-4 cancel each other out leaving

lim x->64 = 1/u^2+4u+16

1/64^2+4(64)=16

oddly i find the number to large am i doing this right?

1. 👍
2. 👎
3. 👁
4. ℹ️
5. 🚩
1. * 1/64^2+4(64)+16

1. 👍
2. 👎
3. ℹ️
4. 🚩
2. let ∛x = u
then x = u^3
and as x---> 64, u ---> 4

lim (∛x-4)/(x-64) , as x --->64
= lim (u - 4)/(u^3 - 64) , as u ---> 4
= lim (u-4)((u-4)(u^2 + 4u + 16) , u -->4
= lim 1/(u^2 + 4u + 16), as u --> 4
= 1/(16 + 16 + 16)
= 1/48

When you make your switch from x to u, you also have to make the change in the approach value

1. 👍
2. 👎
3. ℹ️
4. 🚩
3. Ok thanks for the help,it helped a lot!!!

1. 👍
2. 👎
3. ℹ️
4. 🚩
4. would the lim approaches 64 is it 1/48 or is it when the lim approaches 4 is 1/48

1. 👍
2. 👎
3. ℹ️
4. 🚩
5. For the given substitution , the two statements:

lim (∛x-4)/(x-64) , as x --->64
and
lim (u - 4)/(u^3 - 64) , as u ---> 4

are equivalent, so

lim (∛x-4)/(x-64) , as x --->64
= 1/48
and
lim (u - 4)/(u^3 - 64) , as u ---> 4
= 48

They are equivalent questions, we made them that way using the substitution.

here is a little trick with your calculator.
pick a value of x close to the original approach value
e.g. let x = 64.0001
now sub into the original expression
(∛64.0001 - 4)/(64.0001 - 4)
= .000003083/.0001
= .0208332
and 1/48 = .0208333

I used to encourage my students to use this to check their answer.
You could also do this before you work out the question to predict your answer.

1. 👍
2. 👎
3. ℹ️
4. 🚩

## Similar Questions

1. ### Probability

Let Sn be the number of successes in n independent Bernoulli trials, where the probability of success at each trial is 1/3. Provide a numerical value, to a precision of 3 decimal places, for each of the following limits. You may

2. ### calculus again

Suppose lim x->0 {g(x)-g(0)} / x = 1. It follows necesarily that a. g is not defined at x=0 b. the limit of g(x) as x approaches equals 1 c.g is not continuous at x=0 d.g'(0) = 1 The answer is d, can someone please explain how?

3. ### No one is helping me :/ ??

If y = 3 is a horizontal asymptote of a rational function, which must be true? lim x→ 3 f(x) = 0

4. ### Algebra 2

If y=3 is a horizontal asymptote of a rational function, which must be true? lim x→ 3 f(x) = 0 lim x→ 0 f(x) = 3 **my answer lim x→ ∞ f(x) = 3 lim x→ 3 f(x) = ∞

1. Evaluate: lim x->infinity(x^4-7x+9)/(4+5x+x^3) 0 1/4 1 4 ***The limit does not exist. 2. Evaluate: lim x->infinity (2^x+x^3)/(x^2+3^x) 0 1 3/2 ***2/3 The limit does not exist. 3. lim x->0 (x^3-7x+9)/(4^x+x^3) 0 1/4 1 ***9 The

2. ### Calculus

Let f be a function defined for all real numbers. Which of the following statements must be true about f? Which might be true? Which must be false? Justify your answers. (a) lim of f(x) as x approaches a = f(a) (b) If the lim of

3. ### Probability

Let Sn be the number of successes in n independent Bernoulli trials, where the probability of success for each trial is 1/2 . Provide a numerical value, to a precision of 3 decimal places, for each of the following limits. 1. lim

4. ### calc bc (condensed

is the limit as x approaches 0 of sin3x over 3x equal to zero? sorry-- basically this is my problem: lim [sin 3x / 4x) x-> 0 ~~~~I multiplied& eventually got to .75* lim (sin 3x / 3x) x-> 0 ~so i figured since (lim (sinx/x) x-> 0

1. ### Calculus

For the function f whose graph is given, state the following (a) lim x → ∞ f(x) (b) lim x → −∞ f(x) (c) lim x → 1 f(x) (d) lim x → 3 f(x) (e) the equations of the asymptotes (Enter your answers as a comma-separated

2. ### Math

True or False If lim x→∞ f(x) = 1and lim x→∞ g(x) = ∞,then lim x→∞ [f(x)]^g(x) = 1.

3. ### Calculus Limits

Question: If lim(f(x)/x)=-5 as x approaches 0, then lim(x^2(f(-1/x^2))) as x approaches infinity is equal to (a) 5 (b) -5 (c) -infinity (d) 1/5 (e) none of these The answer key says (a) 5. So this is what I know: Since

4. ### calculus

if i define the function f(x)= x^3-x^2-3x-1 and h(x) = f(x)/g(x), then evaluate the limit (3h(x)+f(x)-2g(x), assuming you know the following things about h(x): h is continuous everywhere except when x = -1 lim as x approaches